Fox's book of martyrs: a history of the lives, sufferings and triumphant deaths of the early Christian and the Protestant martyrs - Foxe, John (John C. Winston Co., 1926)
History of Christian martyrs to the first general persecution under Nero -- The ten primitive persecutions -- Persecutions of the Christians in Persia -- Papal persecutions -- An account of the Inquisition -- An account of the persecutions in Italy under the papacy -- An account of the life and persecutions of John Wycliffe -- An account of the persecutions in Bohemia under the papacy -- An account of the life and persecutions of Martin Luther -- General persecutions in Germany -- An account of the persecutions in the Netherlands -- The life and story of the true servant and martyr of God, William Tyndale -- An account of the life of John Calvin -- An account of the persecutions in Great Britain and Ireland, prior to the reign of Queen Mary I -- An account of the persecutions in Scotland during the reign of Henry VIII -- Persecutions in England during the reign of Queen Mary -- Rise and progress of the Protestant religion in Ireland; with an account of the barbarous massacres of 1641 -- The rise, progress, persecutions, and sufferings of the Quakers -- An account of the life and persecutions of John Bunyan -- An account of the life of John Wesley -- Persecutions of the French Protestants in the south of France, during the years 1814 and 1820 -- The beginnings of American foreign missions.